Motywy historiozoficzne w twórczości Fiodora Stiepuna - Marcin Ziomek (Studia Rossica Posnaniensia)
The aim of the article is to introduce the historiosophical views of Fyodor Stepun, one of the most prominent representatives of Russian emigration. In the 1920s, this thinker published a series of ten articles entitled Thoughts on Russia, which attempted to describe the Bolshevik revolution in the broadest possible sociocultural context. Thoughts on Russia are among the first texts interpreting the revolution in historiosophical terms.